Total Synthesis of (−)‐HM‐3 and (−)‐HM‐4 Using an Asymmetric Gold‐Catalyzed [3, 3]‐Sigmatropic Rearrangement of Sulfonium. Issue 17 (12th April 2023) - Zhou, Weiping; Voituriez, Arnaud
Abstract: The asymmetric total synthesis of two sesquiterpenoids, (−)‐HM‐3 and (−)‐HM‐4, isolated from a phytopathogenic fungus, has been developed using a gold‐catalyzed [3, 3]‐sigmatropic rearrangement of sulfonium as key step. During this transformation, an excellent chirality transfer was observed between the chiral sulfoxide substrate and the newly formed quaternary stereogenic center with 96 % enantiomeric excess. The implementation of this efficient methodology allowed us to isolate the two natural products in only 7–8 chemical steps with overall yields reaching 12–16 %. Abstract : Asymmetric total syntheses of two sesquiterpenoids, (−)‐HM‐3 and (−)‐HM‐4, were accomplished using a gold‐catalyzed [3, 3]‐sigmatropic rearrangement of sulfonium as key step. This stereospecific transformation allowed the access to these two natural products in only 7–8 chemical steps.